Selective head–neck cooling after concussion shortens return-to-play in ice hockey players - Anna Gard; Yelverton Tegner; Mohammad Fazel Bakhsheshi; Niklas Marklund (Concussion, 2021)
We aimed to investigate whether selective head–neck cooling could shorten recovery after sports-related concussions (SRCs). In a nonrandomized study of 15 Swedish professional ice hockey teams, 29 ...